Biocontrol of Grey Mold on Strawberry Fruit by Bacillus spp. and Study of the Mechanisms Involved - Ilham Barakat; Noureddine Chtaina; Kaoutar Caidi; Fatiha Bentata (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Grey mold, caused by the fungus Botrytis cinerea, is one of the most prevalent diseases affecting strawberry plants (Fragaria ananassa). The objective of this study was to assess the antagonistic effect of 5 bacterial strains belonging to the genus Bacillus spp. (BA1, BF2, BB3, BI3, and BO4) against B. cinerea, tested both in vitro and in vivo on strawberry fruits. The strains exhibited antifungal activity against B. cinerea under in vitro conditions, both through direct confrontations and antibiosis tests, as well as through the effect of organic compounds. Strain BO4 could inhibit mycelial growth by 62.92% through direct confrontation and 64.58% through the secretion of volatile organic compounds. Additionally, the strain BF2 demonstrated a high antibiosis effect (74.64%) compared to the control at a concentration of 25%. Treating fruits with the bacterial suspension and culture filtrate of the 5 studied strains controlled grey mold growth in vivo, as indicated by low severity indices in strawberries treated with strains BI3, BF2, and BA1, marked by percentages of 24.44%, 24.44%, and 37.78%, respectively, for preventive treatment. The difference in the effectiveness of various strains depended on the treatment mode; preventive treatment proved to be more effective compared to curative treatment.